Kepemimpinan Pembina Madrasah Diniyah Hidayatul Mubtadi’ien Ngawi Berbasis Kecerdasan Emosional dalam Menyongsong Era Globalisasi - Arika Oernika Mahanani; Ana Minniswatil Maghfiroh; Nur Efendi (Al-fahim : Jurnal Manajemen Pendidikan Islam, 2024)
Leadership is a crucial aspect that needs to be considered in education, as effective leadership can provide educational outcomes that align with the demands of the times. This article is examined with the aim of describing the leadership model based on emotional intelligence in facing the era of globalization in the Hidayatul Mubtadi'ien Ngawi Islamic school. The research uses a qualitative approach with a case study type, and primary data sources include madrasah diniyah facilitators, the head of the madrasah diniyah, and representative diniyah teachers. Data collection techniques involve observation, interviews, and documentation. The data analysis process includes data condensation, data display, and drawing conclusions. The research results show that in preparation for the era of globalization, the Hidayatul Mubtadi'ien Ngawi Islamic elementary school management has introduced a new innovation by merging institutions while emphasizing the key elements of leadership in personal competence and social competence dimensions.